?SCREENING ELITE HYBRIDS OF COTTON GOSSYPIUM HIRSUTUM L. (Biological Sciences - PJSIR, 1998)
Study on heterosis was carried out on 15 hybrid combinations involving eight Gossypium hirsutum L. varieties. Six hybrids showed significant differences in all types of heterosis ror attributes like boll number and seed couon yield per plant and one hybrid showed heterosis for boll weight. None of the hybrids shuwed significant increase over parent. for syrnpodia per plant. The hybrid S-12 x CRIS-S2 exhibited maximum heterosis over commercial cultivar (183.76%). The crosses S·12 x CRIS-S2 and CRTS·7A NIAB·78 showed promising performance 1'01' the characters like boll number and seed couon yield and are recommended to be included in breeding programmes to develop high yielding varieties/ hybrids.